Kursi Lantai dan Penataan Layout Meningkatkan Work Engagement dan Produktivitas Pekerja Pembuatan Atap Alang-Alang - I Kadek Dwi Arta Saputra; Susy Purnawati; Ida Bagus Alit Swamardika; Luh Made Indah Sri Handari Adiputra; I Gusti Ngurah Priambadi; I Made Krisna Dinata (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
Workers making reeds roofs work with a working posture sitting on the floor with a slightly bent back. Intervention by giving floor chairs as a base during work as well as structuring the production process layout. This study aims to improve work engagement and productivity of workers making reeds roofs in Gianyar. The research design used was experimental with randomized pre-posttest control group design involving 16 randomly selected research samples. The subjects in this study were divided into two groups: the control group were workers who worked as usual and the treatment group were workers who worked using floor chairs and structuring the production process layout. Work engagement was recorded using the UWES 17 questionnaire and productivity was recorded from the number of Imperata roofs produced. Data analysis used parametric tests with a value of ? 0.05 for normally distributed data and non-parametric tests for data that were not normally distributed. The results showed a significant difference in work engagement and productivity (p<0.05). In the control group the mean score of work engagement was 50.75 and the productivity was 0.067. Whereas in the treatment group the average score of work engagement was 71.12 and productivity was 0.015. Giving floor chairs and structuring the layout of the production process is proven to increase work engagement by 40.13% and increase productivity by 34.60%. It can be concluded that the application of ergonomics in the form of providing floor chairs and structuring the layout of the production process is proven to increase work engagement and work productivity in workers making reeds roofs.